Treatment of osteoporosis with parathyroid peptide (hPTH 1-34) and oestrogen: increase in volumetric density of iliac cancellous bone may depend on reduced trabecular spacing as well as increased thickness of packets of newly formed bone. - Bradbeer, J; Arlot, M; Meunier, P; Reeve, J (1992)
OBJECTIVE: We wished to determine whether treatment of vertebral osteoporosis with human parathyroid peptide 1-34 (hPTH 1-34), given as a daily injection with supplementary treatment with hormone replacement therapy (HRT), increases cancellous bone area in the ilium by increasing the size of packets of new bone. DESIGN AND MEASUREMENTS: The width of packets of cancellous bone (wall width) was measured at random intercepts and mean values calculated. Cancellous bone area and perimeter were also measured. Indices of trabecular separation and the complementary quantity trabecular number were derived according to Parfitt's method, as well as trabecular width. Patients were used as their own controls and changes in these indices calculated. Correlations were calculated for data obtained from independent measurements. PATIENTS: We studied eleven women with post-menopausal osteoporosis, diagnosed by fractures after exclusion of causes of secondary osteoporosis. RESULTS: One woman did not comply with her HRT therapy. In the others, treatment with hPTH 1-34 + HRT restored the characteristically depressed pre-treatment values of wall width to normal. Trabecular width increased approximately four times more than wall width. Changes in wall width correlated with changes in cancellous bone area; however, bone area increased considerably more than could be accounted for statistically by changes in wall width. A decrease in trabecular separation was found to account for the additional increase in bone area (P = 0.056). CONCLUSION: hPTH 1-34 + oestrogen and progestagen therapy increases the width of packets of new cancellous bone with consequent increases in the width of trabecular plates.